Efforts to Improve Students' Ability to Memorize the Quran, Surah Asy-Syams, through the Tikrar Method at SD Negeri 4 Meurah Dua - Bahri, Samsul; Faridah (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Classroom Action Research was carried out at SD Negeri 4 Meurah Dua with a research subject that focused on grade V students totaling 22 students. This research is based on the low learning outcomes of students in memorization. Based on the initial observations made previously, the learning process carried out by the previous students was to memorize themselves individually without the guidance of the teacher, so that students were less courageous and confident in the results of their memorization. Another factor that becomes a problem in the memorization process is the lack of repetition. Therefore, the tikrar method is very suitable in an effort to improve the memorization ability of students of the Quran letter Ash-Shams in Class V of SD Negeri 4 Meurah Dua, Pidie Jaya Regency, Academic Year 2024/2025. The implementation of learning has also increased, namely in the first cycle it reached 45.45% and in the second cycle it increased to 86.36%. Based on these results, the application of the tikrar method to the material of the Qur'an surah Ash-Shams showed an increase in student learning outcomes. Likewise, the results of observation, in the first cycle 83% were obtained and in the second cycle it increased to 92.22%. The level of success of student activities based on the observations of the two observers is included in the very good category.